ADSORBSI GAS KARBON MONOKSIDA (CO) DALAM RUANGAN DENGAN KARBON AKTIF TEMPURUNG KELAPA DAN KULIT DURIAN - Ulfa Nurullita; Mifbakhuddin - (Universitas Muhammadiyah Semarang, 2015)
Cigarettes contain more than 4000 elements and at least 200 of them are harmful to health. The main toxins in cigarettes are tar, nicotine, and carbon monoxide. The purpose of this study was to know the ability of coconut shell and durian skin activated carbon as adsorbent of carbon monoxide. The study was pre-experimental with Randomized control group only design. Independent variable is the type of activated carbon (coconut shell, durian skin, and contol), the dependent variable is the concentration of carbon monoxide. This is laboratory-scale research. The results showed the lowest concentration of carbon monoxide in the treatment with activated carbon durian skin that 29 ppm. The average of carbon monoxide concentration decrease (than the control group) on coconut shell group 68,7 ppm, while the average of durian skin is 77,478 ppm. One way anova test results to see the difference in the concentration of carbon monoxide in various types of activated carbon p value 0,000 while independent t test to see the difference carbon monoxide reduction between coconut shell and durian skin activated carbon with p value is 0,000. Conclusion: there is a differences adsorbtion of carbon monoxide between coconut shell and durian skin activated carbon.Keywords: carbon monoxide, activated carbon, coconut shell, durian skin